THE EFFECT OF Administering MAGGOT FLOUR (Hermetia illucens) IN COMMERCIAL FEEDING ON PATIN FISH SEEDS (Pangasianodon hypophthalmus) - Gunawan; Adli Waliul Perdana; Iko Imelda Arisa; Iswandi; Rahmi (Jurnal Penelitian Progresif, 2023)
One of Indonesia's fishery commodities that has bright prospects for development is catfish (Oreochromis niloticus) which has been known for a long time, grows relatively quickly and has a good response to its environment so it is very easy to cultivate. Fisheries statistics data from the Directorate General of Aquaculture for 2018 states that catfish production increases every year. In 2014 it was 999,695 tons, in 2015 it was 1,084,281 tons, in 2016 and 2017 it was 1,114,156 tons, catfish production reached 4,463,333 tons in the last five years. The experimental design used in this research was a randomized design with 4 treatments and 3 repetitions. The treatments are: Treatment MK46 (Feeding 40% maggot and 60% commercial), Treatment MK55 (Feeding 50% maggot and 50% commercial), Treatment MK64 (Feeding 60% maggot and 40% commercial) and Treatment K (Giving 100% commercial feed). The data obtained was then analyzed using analysis of variance (ANOVA). Based on the research results, it showed that the highest length growth was in the MK55 treatment with a patini of 3.50 ± 0.10b. The highest weight growth was in the MK55 treatment with patini 4.40 ± 0.111b. The highest specific growth rate was obtained by MK55 treatment with patini 3.78 ± 0.017b. The highest feed efficiency was obtained in the MK55 treatment with patini of 77.67 ± 2.082b, while the highest survival rate was obtained in the MK46 treatment with patini of 83.33 ± 3.512a.